2015
DOI: 10.1111/trf.13100
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effectiveness of plasma prepared with amotosalen‐UVA pathogen inactivation and conventional plasma for support of liver transplantation

Abstract: BACKGROUND Liver transplant may require large‐volume plasma transfusion with increased risk of transfusion‐transmitted infection (TTI). Pathogen inactivation of plasma with amotosalen‐UVA offers the potential to mitigate TTI risk. STUDY DESIGN AND METHODS A retrospective cohort design was used to compare the therapeutic efficacy and key safety outcomes for liver transplants supported with quarantine plasma (Q‐FFP [reference]) or amotosalen‐UVA plasma (IBS plasma [test]). The outcomes evaluated were volume of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 30 publications
1
18
0
Order By: Relevance
“…Our clinical observations reported here for amotosalen/UVA‐treated platelets in the MT setting argue strongly against this hypothesis and instead support the safety and efficacy of these components in patients requiring MT. Furthermore, the comparative effectiveness studies of amotosalen/UVA‐treated and conventional plasma in general liver transplantation, including those that required MT, similarly suggested that pathogen reduction in plasma did not adversely affect outcomes . While our study included only a small number of trauma patients, the high mortality in all non‐liver transplant patients with MT supports a similar haemorrhagic risk profile as is seen in trauma.…”
Section: Discussionsupporting
confidence: 51%
See 3 more Smart Citations
“…Our clinical observations reported here for amotosalen/UVA‐treated platelets in the MT setting argue strongly against this hypothesis and instead support the safety and efficacy of these components in patients requiring MT. Furthermore, the comparative effectiveness studies of amotosalen/UVA‐treated and conventional plasma in general liver transplantation, including those that required MT, similarly suggested that pathogen reduction in plasma did not adversely affect outcomes . While our study included only a small number of trauma patients, the high mortality in all non‐liver transplant patients with MT supports a similar haemorrhagic risk profile as is seen in trauma.…”
Section: Discussionsupporting
confidence: 51%
“…The low overall in‐hospital mortality rate [4/93 patients (4·3%)] despite the need for MT is reflective of the elective nature of liver transplant surgery, and speaks to the effectiveness of massive transfusion strategies that now include pathogen‐reduced PC. A similar study previously showed that plasma treated with the amotosalen/UVA process was equivalent to conventional plasma in the liver transplantation setting .…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…Additional, larger phase IV retrospective clinical studies have been successfully performed in the TTP and liver transplantation settings [23,24]. The set of clinical trials performed encompasses most of the routine applications for INTERCEPT treated plasma.…”
Section: Clinical Experiencementioning
confidence: 99%